Academic Service Quality Management For The Quality Of First High School Graduates (Case Study Of SMPN 1 Kresek And SMPN 1 Mauk) - Gunawan, Endra; Sauri, Sofyan; Hanafiah, Hanafiah; Koswara, Nandang (International Journal of Educational Research & Social Sciences, 2022)
One of the causes of the low quality of education graduates in Indonesia is the low quality management of academic services in schools, especially in State Junior High Schools. The low quality of graduates in junior high schools is due to common mistakes made by principals in managing education so that the quality of junior high schoolgraduates is low, including: (1) principals lead with a weak vision and mission; (2) the principal as a leader who lacks innovation in educational programs; (3) Principals lead without utilizing technology in the learning process; (4) Principals lead by ignoring social networks; (5) The principal does not provide creative space for teachers and students; (6) The principal does not use conflict as a driver of progress. In this regard, the researchers chose the title of the study, namely "Academic service quality management for the quality of State Junior High School (SMP) graduates. This research was conducted on principals, teachers, and students at SMP Negeri 1 Kresek, SMP Negeri 1 Mauk, Kab. Tangerang. This study focuses on management functions which include: Planning (Planning), Actuating, Evaluation (Evaluating), Supporting and Inhibiting Factors, and Efforts to overcome the obstacles. The approach used in this study is a qualitative approach, while the research method used is descriptive analytic method. Data collection techniques in this study are: interviews, observation, and documentation. The conclusions of the research conducted by the researchers are: the implementation of management carried out by the two principals concerning Planning, Actuating, Evaluation, Supporting and Inhibiting Factors, and Efforts to overcome obstacles in SMP Negeri 1 Kresek , SMP Negeri 1 Mauk, Kab. Tangerang has been implemented but not optimally because there are still many elements in the above activities that there is still no synchronization, integration, and simultaneous in accordance with the vision and mission of each school. However, in general the quality management of the principal's academic services has been running quite well in accordance with the conditions of each school as seen from the achievements of the school program implementation as stated below: According to the principal of SMP Negeri 1 Kresek that the implementation of the school program has been achieved ranged from 75-80%, while for SMP Negeri 1 Mauk the achievement of school program implementation reached 80%, Tangerang Regency the achievement of the implementation of school academic service programs reached about 80% which had an impact on the quality of graduates.